(3cJGH GdWHbGJ ef JNQjL eSdes - (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf, CHh GdMSjf,J (B261 (3g` s ((3CHhHcQ Hf Ydi Hf Hf ESeGYjd GdCfUGQi GdTGaYi GdHgfSi s)
(3ChdgG (B:s
(3MOKfG CHh eMeO YHOGddg Hf eMeO Hf eMeO GdTeGSi s
(3BNQgG (B:s
(3ced cJGH GdWHbGJ ef JNQjL eSde hHg ced LejY GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B279 (3C (B- (3U(B297 (3Hs
(3jPcQ JSejI ef Qhi Yf QShd Gddg Udi Gddg Ydjg hSde ef GdPjf UMHhg hef Qhi Yfg Udi Gddg Ydjg hSde eef QBg hde jUMHg dUZQ Sfg Ch fCi OGQgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3JNQjL s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs